Efficacy and safety of XELOX combined with neoadjuvant radiotherapy versus neoadjuvant chemotherapy in locally advanced gastric cancer - Shanshan Bu; Siyi Wang; Ting Wang; Hang Xing; Yue Cao; Zhandong Zhang; Chuang Shang; Xiance Tang; Yifei Liu; Xiaoqun Dong; Xiushen Wang (BMC Cancer)
Abstract Background The work aimed to compare the efficacy and safety of chemotherapy regimen (oxaliplatin + capecitabine, XELOX) combined with neoadjuvant radiotherapy (NART) and neoadjuvant chemotherapy (NACT) in locally advanced gastric cancer. Methods We retrospectively analyzed clinical data from patients with locally advanced gastric cancer who underwent radical gastrectomy with D2 lymph node dissection at our center between January 2019 and December 2020. The study compared tumor markers, postoperative pathology, short-term efficacy, postoperative complications, and hospital stay between the chemoradiotherapy (CRT, XELOX + NART) group and the NACT-only group. Pearson correlation coefficients was used to analyze the correlations between clinical variables and tumor biomarkers. Inverse probability weighting (IPW) was used to adjust for confounding factors. Results A total of 409 patients were included, with 369 (90.2%) in the NACT group and 40 (9.8%) in the CRT group. Significant correlations were found between clinical variables and tumor biomarkers, which may help identify potential prognostic factors for gastric cancer treatment. After IPW adjustment, baseline characteristics were similar between groups. The negative conversion rate of CEA-positive patients was significantly higher in the CRT group (38.1% vs. 11.8%, P < 0.001). The rate of pathological complete response was also higher in the CRT group (15.8% vs. 4.7%, P = 0.017). Postoperative pathological stages ypT0 and T1 were observed in 35.5% of the CRT group compared to 13.5% in the NACT group (P = 0.031). The CRT group had a lower average number of lymph nodes dissected (17 vs. 24, P < 0.001) but a higher ypN0 rate (60.3% vs. 39.8%, P = 0.024). The proportion of patients with tumor regression grade (TRG) 0–1 was higher in the CRT group (60.3% vs. 24.3%, P = 0.003). The R0 resection rate after IPW was 100% in the CRT group versus 96.5% in the NACT group (P = 0.001). No significant differences were found between the CRT and NACT groups in nerve invasion, vascular embolus, peritoneal invasion, bone marrow suppression, nausea, vomiting, esophagitis, diarrhea, other adverse reactions, postoperative complications, or average hospitalization time. The CRT group showed superior disease-free survival while no overall survival advantage (P < 0.05). Conclusions The XELOX regimen combined with neoadjuvant chemoradiotherapy provided superior downstaging, short-term pathological response, and local control benifits compared to perioperative chemotherapy alone, with similar surgical safety profiles.